Assessment of physical fitness parameters in Olympic clay target shooters and their relationship with shooting performance - Peljha, Z.; Michaelides, M.; Collins, D.; Carson, H. J. (Journal of Physical Education and Sport, 2021)
Problem Statement: There is an noticable absence of scientific research on the role of certain physical fitness parameters in Olympic clay target shooting. Purpose: The objective of this exploratory study was to identify the relationships between selected anthropometric and fitness parameters with shooting performance of Olympic clay target shooters and any differences based on skill level. Approach: Nineteen Cyprus shooting federation members of beginner (n = 11) and national-level (n = 8) abilities for both skeet and trap participated. Shooting results were tested for association with anthropometrics, reaction time, balance, posterior muscle chain flexibility, shoulder mobility, grip strength, upper-body strength endurance, trunk flexion/extension strength and cardiopulmonary fitness. Results: Bivariate Pearson`s correlation coefficient tests showed significant, strong and moderate correlations between shooting performance and bilateral symmetry in shoulder mobility (r = 0.80, p < 0.001) and handgrip strength (r = 0.61, p = 0.01). When accounting for skill level, elites demonstrated significant differences in height (t(17) = -2.76, p = 0.01; d = 1.29, 95% CIs [172, 178]), mass (t(17) = -2.47, p = 0.03; d = 1.85, 95% CI [68.7, 87.1]), posterior muscle chain flexibility (t(17) = 4.46, p < 0.001; d = 2.04, 95% CI [25.2, 33]), dynamic (t(17) = 3.09, p = 0.01; d = 1.43, 95% CI [31.1, 38.7]) and static balance (t(17) = 0.3, p = 0.01; d = 1.35, 95% CI [41.5, 59.9]). Conclusions: These findings suggest that specific prerequisites may be associated with and, in fact, support being elite. Furthermore, that increasing upper-body symmetries could improve shooting score. As such, this study provides the first empirical evidence across a range of fitness parameters for Olympic clay shooting.